Investigation of Spray Drying Parameters to Formulate Novel Spray-Dried Proliposome Powder Formulations Followed by Their Aerosolization Performance - Iftikhar Khan; Kaylome Edes; Ismail Alsaadi; Mohammed Q. Al-Khaial; Ruba Bnyan; Saeed A. Khan; Sajid K. Sadozai; Wasiq Khan; Sakib Yousaf (Pharmaceutics)
Background: Spray drying, whilst a popularly employed technique for powder formulations, has limited applications for large-scale proliposome manufacture. Objectives: Thus, the aim of this study was to investigate spray drying parameters, such as inlet temperature (80, 120, 160, and 200 °C), airflow rate (357, 473, and 601 L/h) and pump feed rate (5, 15, and 25%), for individual carbohydrate carriers (trehalose, lactose monohydrate (LMH), and mannitol) for 24 spray-dried (SD) formulations (F1–F24). Methods: Following optimization, the SD parameters were trialed on proliposome formulations based on the same carriers and named as spray-dried proliposome (SDP) formulations. Drug delivery of the formulations was assessed using a dry powder inhaler (DPI) in combination with a next-generation impactor (NGI). Results: Upon analysis, formulations F6 (SD-mannitol), F15 (SD-trehalose), and F20 (SD-LMH) demonstrated high production yields (84.01 ± 3.25, 72.55 ± 5.42, and 70.03 ± 3.39%, respectively), small particle sizes (2.96 ± 1.42, 4.55 ± 0.46, and 5.16 ± 1.32 µm, respectively) and low moisture contents (0.25 ± 0.03, 3.76 ± 0.75, and 1.99 ± 0.77%). These SD optimized parameters were then employed for SDP formulations employing dimyristoly phosphatidylcholine (DMPC) as a phospholipid and beclomethasone dipropionate (BDP) as the model drug. Upon spray drying, SDP-mannitol provided the highest production yield (82.45%) and smallest particle size (2.64 µm), as well as high entrapment efficiency (98%) and a high fine particle dose, fine particle fraction, and respirable fraction (285.81 µg, 56.84%, 86.44%, respectively). Conclusions: The study results are a promising step in the optimization of the large-scale manufacture of proliposome formulations and highlight the versatility of the instrument and variability of formulation properties with respect to the carriers employed for targeting the pulmonary system using dry powder inhalers.